On holiday : a history of vacationing - Löfgren, Orvar (California studies in critical human geography ;, 1999)
"When it comes to holidays, some talk about "seeing the world," others about "getting away from it all." These two basic philosophies of travel are elaborated delightfully in Orvar Lofgren's investigation of "elsewhereness" as a human pursuit. Whether we set out in search of a mountainscape that will take our breath away, artifacts of the past to enrich our minds, the purest sand on the most unspoiled beach, or a summer place to know and cherish, we follow inner itineraries as time-honored and various as the routes we take." "Beginning his cultural journey among some eighteenth-century pioneers of tourism, Lofgren takes us on a tour of the Western holiday world and shows how two centuries of "learning to be a tourist" have shaped our own ways of vacationing. From country walks in search of the picturesque to wilderness trekking for more grandiose views, from seasonal campsites and communities on the coasts of New England and Sweden to Mediterranean resorts and rearranged ruins, from Continental spas to Las Vegas megahotels, we see how fashions in destinations have changed through the years, with popular images (written, drawn, painted, and later photographed) teaching the tourist what to look for and how to experience it."